Beta-sitosterol glycoside from Paraboea leuserensis and Cytotoxicity Test against MCF-7 Human Breast Cancer Cells - Harfita, Nur Laily; Santoni, Adlis; Suryati, Suryati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Paraboea leuserensis, a plant endemic to the Leuser Mountain in the provinces of Aceh and North Sumatra, has been traditionally used for medicinal purposes by chewing or boiling, addressing conditions such as stomachaches and providing stamina enhancement. This study aimed to isolate secondary metabolite compounds from Paraboea leuserensis and conduct in vitro anticancer tests. Method: The ethyl acetate extract was isolated through column chromatography, yielding beta-sitosterol glycoside, and was tested for bioactivity against human breast cancer cells MCF-7 using the MTT method. Results: The compound demonstrated activity against breast cancer cells (MCF-7) with an IC50 value of 24.83 mg/L. Conclusion: Paraboea leuserensis exhibits potential anticancer activity. The isolation of beta-sitosterol glycoside from the plant and its demonstrated activity against MCF-7 human breast cancer cells suggest a promising avenue for further exploration of the plant's anticancer properties.